Stamping of a Cross-shaped Part with 5052, 5754 and 6016 Aluminum Alloy Sheets – Experimental and Finite Element Analysis Comparison. (May 2019) - Esmaeilpour, R; Tiji, S A Nazari; Kim, H; Park, T; Kim, H; Pourboghrat, F; Mohammed, B
Abstract: The application of aluminum alloys is continuing to increase in automotive and aerospace industries. In this study, the stamping of a cross-shaped part, representing typical deep drawn automotive parts, was attempted with three different types of aluminum alloy sheets. To characterize the anisotropic properties of the material, uniaxial tensile tests were performed with ASTM standard dog-bone specimens cut from AA5052, AA5754 and AA6016 T4 alloy sheets. The stamping of the cross-shaped parts was conducted using a high capacity servo press with a servo-cushion system. Deformation strains developing in stamped parts were measured with the ARGUS system for comparison with finite element simulation results. Formed parts were also cut in two different directions using a water-jet machine, and thickness variations along the length of the cut section were measured. The measured surface strains and thickness distributions were compared with finite element simulations results obtained with LS-Dyna explicit code using the Yld2000-2D and Hill's 48 yield functions. Overall, experimental and numerical results correlated well, especially with the Yld2000-2D yield function, implying that this yield function is well suited for the modeling of the complex cross-shaped parts with aluminum alloys.